Light irradiance and spectral distribution effects on cyanobacterial hydrogen production - Salleh S.F.; Kamaruddin A.; Uzir M.H.; Mohamed A.R.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
Productivity; Different lights; Energy source; Heterocystous cyanobacterium; Hydrogen production rate; Light irradiances; Light spectrum; Photosynthetic productivity; Spectral distribution; Hydrogen production; accumulation; cyanobacterium; flight; hydrogen; light effect; photosynthesis; spectrum; Cyanobacteria